Review of wave power system development and research on triboelectric nano power systems - Yan, Jin; Mei, Naerduo; Zhang, DaPeng; Zhong, Yinghao; Wang, Cheng (Frontiers in Energy Research, 2022)
With its huge energy storage and high energy density, ocean wave energy is one of the most promising marine renewable resources. Traditional wave energy generation technology, on the other hand, has a high maintenance cost, a bulky construction, and a low conversion efficiency, which limits its application. Due to its low cost, simple construction, and ease of fabrication, wave energy generating technology based on triboelectric nanogenerators has emerged as a potential new power generation technology in recent years. This paper elaborates on the power generation principle, working mode, and the latest research status of wave energy harvesting using different types of triboelectric nanogenerator structures, and finally summarises the current problems and challenges of this technology, and innovatively combines some current examples to propose future research trends, which can help relevant reseach. This will assist researchers in swiftly grasping the present state of wave energy harvesting research and promoting the field’s progress.